2008
DOI: 10.1134/s0006297908020053
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial free radical production induced by glucose deprivation in cerebellar granule neurons

Abstract: Using a fluorescent probe for superoxide, hydroethidine, we have demonstrated that glucose deprivation (GD) activates production of reactive oxygen species (ROS) in cultured cerebellar granule neurons. ROS production was insensitive to the blockade of ionotropic glutamate channels by MK-801 (10 microM) and NBQX (10 microM). Inhibitors of mitochondrial electron transport, i.e. rotenone (complex I), antimycin A (complex III), or sodium azide (complex IV), an inhibitor of mitochondrial ATP synthase--oligomycin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Selective increase in lipo‐peroxidation due to hypoglycemia leads to oxidative stress that has been confirmed in animal studies . Animal studies have also confirmed increased mitochondrial ROS production during both hypoglycemia and in cultured neurons during glucose deprivation . ROS are also known to activate several intermediates of thrombosis, including platelets .…”
Section: The Effect Of Hypoglycemia On Procoagulant Mechanismsmentioning
confidence: 84%
“…Selective increase in lipo‐peroxidation due to hypoglycemia leads to oxidative stress that has been confirmed in animal studies . Animal studies have also confirmed increased mitochondrial ROS production during both hypoglycemia and in cultured neurons during glucose deprivation . ROS are also known to activate several intermediates of thrombosis, including platelets .…”
Section: The Effect Of Hypoglycemia On Procoagulant Mechanismsmentioning
confidence: 84%
“…Previously, sphingolipids have been shown to inhibit glucose uptake, 32, 33 which could in turn induce oxidative stress. 34 These reports provided the basis for us to hypothesize that safingol, a synthetic sphingolipid, might be able to inhibit glucose uptake. Using a fluorescent derivative of glucose, 2-( N -(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-2-deoxyglucose (2-NBDG), the uptake was probed in MDA-MB-231 and HT-29 cells.…”
Section: Resultsmentioning
confidence: 99%
“…39 Similarly, glucose deprivation was shown to initiate oxidative stress and increase mitochondria production of ROS, as demonstrated in lung cancer cells A549, brain cells, retina cells and adrenal cells. 34 Although several in vivo studies supported the upstream role of ROS in activating AMPK, 40 this remains to be determined in safingol-treated cells. AMPK is not only known as an energy sensor, but also reported to have a role in inducing autophagy through the suppression of mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged hypoxia and glucose deprivation are key components of ischemia in bodily tissues as a significant driver of elevated mitochondrial ROS production and this has been well described in the context of myocardial disease (Valko et al, 2007;Chen et al, 2008). Although studies of primary cultured cells specifically examining the effects of low glucose or glucose deprivation (hypoglycaemic conditions) on the induction of mitochondrial ROS production have not been extensively reported, it has been shown to occur, inducing cytotoxicity in neuronal cells Liu, 2006, 2007;Isaev et al, 2008) and in pancreatic beta islet cells (Martens et al, 2005). A more definitive study addressed the differential susceptibility of cancer cells versus normal cells to glucose deprivation .…”
Section: Hypoxia and Low Glucose Drive Carcinogenesis Via Malignant Mmentioning
confidence: 99%